2021
DOI: 10.1371/journal.pone.0245001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 pandemic among health care workers in a secondary teaching hospital in Spain

Abstract: Background The COVID-19 pandemic has posed a huge challenge to healthcare systems and their personnel worldwide. The study of the impact of SARS-CoV-2 infection among healthcare workers (HCW), through prevalence studies, will let us know viral expansion, individuals at most risk and the most exposed areas in healthcare organizations. The aim of this study is to gauge the impact of SARS-CoV-2 pandemic in our hospital workforce and identify groups and areas at increased risk. Methods and findings This is a cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
2
13
1
4
Order By: Relevance
“…Our results concur well with the 15.8 and 19.9% of prevalence of SARS-CoV-2 infection among healthcare workers founded in Kasr Al-Aini University Hospital, Cairo University, and Hospital Universitario de Fuenlabrada, respectively. 24 , 25 Reports from various countries show different seroprevalence of SARS-CoV2 patterns among healthcare workers (HCWs), with an 8.7% in the meta-analysis by Galanis et al, being higher in studies conducted in North America (12.7%) compared to those in Europe (8.5%), Africa (8.2%) and Asia (4%). 26 …”
Section: Discussionmentioning
confidence: 99%
“…Our results concur well with the 15.8 and 19.9% of prevalence of SARS-CoV-2 infection among healthcare workers founded in Kasr Al-Aini University Hospital, Cairo University, and Hospital Universitario de Fuenlabrada, respectively. 24 , 25 Reports from various countries show different seroprevalence of SARS-CoV2 patterns among healthcare workers (HCWs), with an 8.7% in the meta-analysis by Galanis et al, being higher in studies conducted in North America (12.7%) compared to those in Europe (8.5%), Africa (8.2%) and Asia (4%). 26 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, data from recent studies showed healthcare workers are more likely to be exposed to SARS-COV-2 [9] and are, therefore, at higher risk of COVID-19 infection than the general community [10]. Hence, the impact of the COVID-19 pandemic on healthcare workers has been enormous [11]. However, prevention remains the best weapon for protecting healthcare workers against the COVID-19 pandemic [12].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, school boards and teachers, who typically work in high-risk congregate settings, are taking actions to prevent infections, such as adopting online teaching methods to replace traditional face-to-face classroom environments [ 5 7 ]. However, since the onset of the COVID-19 pandemic, adults and children alike have reported experiencing anxiety-induced depression, post-traumatic stress disorder, and other psychological symptoms [ 8 – 10 ]. The impacts of online lessons on children include poor mental health and widening learning disparities among children in low-income families.…”
Section: Introductionmentioning
confidence: 99%